Analisi Tupoksi Konselor dan Pekerja Sosial dalam Penanganan Kasus Penyalahgunaan NAPZA di Rehabilitasi Medan Plus - Ramadhan Lubis, Rafi; Jauzarafa, Felisa; Janiti Kosagi Br Ginting, Gatri; Yosep Lorenzo Panjaitan, Nicolas (Pengelola Jurnal Politeknik Negeri Ketapang Jl. Rangga Sentap, Dalong Sukaharja, Ketapang 78813. Telp. (0534) 3030686 Kalimantan Barat, 2024)
Drug (Narcotics, Alcohol, and Addictive Substances) abuse is a pressing problem at the global level, including Indonesia. Medical and psychosocial rehabilitation approaches have become the main cornerstones in dealing with individuals caught up in this abuse. In rehabilitation centers such as Medan Plus Rehabilitation, the roles of counselors and social workers play an important role in providing holistic assistance to individuals facing the challenges of drug abuse. This study aims to explore in depth the main tasks and functions (Tupoksi) of counselors and social workers in handling drug abuse cases at Medan Plus Rehabilitation. The research method applied was qualitative using in-depth interviews and participatory observation.The results of the analysis showed that the roles of counselors and social workers are very complex and cover various aspects, ranging from clinical evaluation, preparation of intervention plans, to the provision of individual and group counseling, as well as supervision and assistance during the rehabilitation process.